Cointegrated TFP processes and international business cycles - Pau Rabanal; Juan Francisco Rubio-Ramirez; Vicente Tuesta (Federal Reserve Bank of Atlanta, 2009)
A puzzle in international macroeconomics is that observed real exchange rates are highly volatile. Standard international real business cycle (IRBC) models cannot reproduce this fact. We show that total factor productivity processes for the United States and the rest of the world are characterized by a vector error correction model (VECM) and that adding cointegrated technology shocks to the standard IRBC model helps explaining the observed high real exchange rate volatility. Also, we show that the observed increase of the real exchange rate volatility with respect to output in the past twenty years can be explained by changes in the parameter of the VECM.
Keywords: E32; F32; F33; F41; 330; international business cycles; real exchange rates; cointegration; Weltkonjunktur; Kaufkraftparität; Produktivität; Kointegration; Theorie